Effect of ethanol concentration on the catalytic performance of WO3/MCF-Si and WO3/SBA-15 catalysts toward ethanol dehydration to ethylene - Pantita Trongjitraksa; Mohammad Yazdanpanah; Mohammad Fereidooni; Piyasan Praserthdam; Bunjerd Jongsomjit (South African Journal of Chemical Engineering)
In this study, the WO3/MCF-Si and WO3/SBA-15 catalysts were developed for the ethanol dehydration reaction under different ethanol concentrations including 99, 70, and 50 % v/v in water. It aims to evaluate the effect of water presence in the reaction medium on the catalytic performance and properties of the catalyst which can be applied to developing industrial process. Both catalysts were tested under the vapor phase ethanol dehydration at temperature of 400 °C for 10 h via time on stream. WO3/MCF-Si exhibited superior catalytic activity and greater resistance to both coke formation and water in the feedstock compared to WO3/SBA-15. It was found that variations in ethanol concentrations had negligible influence on the textural properties of the developed catalysts. Nevertheless, a discernible effect on the acidity of the catalyst was observed. Additionally, the use of lower ethanol concentrations (with higher water content) as a feed enhanced the selectivity of ethylene and inhibited the formation of Bronsted acid sites leading to a decrease of coke formation. On the contrary, it also had an adverse effect by attenuating the ethanol conversion. WO3/MCF-Si with using 70 % v/v ethanol as feed demonstrated highest steady-state activity showing the maximal yield of ethylene between 95 and 96.6 %.